Home and Community Care Program : statement of rights and responsibilities. (The Program], 1990)
This paper provides the framework for a complaints policy and procedures in the HACC program and is based on the requirement that both service provider agencies and administering government departments have policies in place to inform consumers of their right to complain, and procedures to resolve any complaints received.